Investigation of Water Tree Degradation in Dry‐Cured and Extruded Three‐Layer (E‐E Type) 6.6‐kV Removed XLPE Cables. Issue 4 (March 2017) - KURIHARA, TAKASHI; TSUTSUI, EIJI; NAKANISHI, EIJI; MAKI, KIYOSHI; MURAKAWA, KENICHI; MORIMOTO, KOJI; TAKAHASHI, TOSHIHIRO; OKAMOTO, TATSUKI
SUMMARY: Dry‐cured and extruded three‐layer (E‐E type) 6.6‐kV cross‐linked polyethylene (XLPE) cables were introduced into electric power systems more than 30 years ago, but they do not experience failures because of water tree degradation. Also, the degradation index of water treeing for these cables has not been established. Therefore, investigating results of residual breakdown voltage and water tree degradation of these cables will help us plan for cable replacement and determine water tree degradation diagnosis scheduling, and will be fundamental data for cable lifetime evaluation. In this study, the authors measured the ac breakdown voltages of dry‐cured and E‐E type 6.6‐kV XLPE cables removed after 18 to 25 years of operation and observed the water trees in their XLPE insulation. As a result, it was observed that breakdown voltages were larger than the maximum operating voltage (6.9 kV) and the ac voltage for the dielectric withstanding test (10.3 kV). Water trees were mainly bow‐tie water trees and their maximum length was approximately 1 mm. Although the number of measured cables was limited, the lifetime of this type of cable was estimated to be approximately 40 years, even experiencing water immersion.